2019
DOI: 10.1186/s40793-019-0341-7
|View full text |Cite
|
Sign up to set email alerts
|

A long-term field experiment demonstrates the influence of tillage on the bacterial potential to produce soil structure-stabilizing agents such as exopolysaccharides and lipopolysaccharides

Abstract: Background: Stable soil aggregates are essential for optimal crop growth and preventing soil erosion. However, tillage is often used in agriculture to loosen the soil, which disrupts the integrity of these aggregates. Soil aggregation can be enhanced by bacteria through their ability to produce exopolysaccharides and lipopolysaccharides. These compounds stabilize soil aggregates by "gluing" soil particles together. However, it has yet to be shown how tillage influences the bacterial potential to produce aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 83 publications
(114 reference statements)
2
33
0
Order By: Relevance
“…This result indicates that the bacterial community grows in abundance, and eventually adapts and stabilizes with agricultural practices. This is in accordance with other studies showing a stable community under long‐term treatments (at least on the DNA level) (de Vries et al , ; Cania et al , ). Moreover, soil organic carbon concentrations peaked at RA6 and decreased at RA12 and RA24 (Pihlap et al , ), likely because organic fertilizers were applied only in the 4th and 7th year of the reclamation process.…”
Section: Discussionsupporting
confidence: 93%
“…This result indicates that the bacterial community grows in abundance, and eventually adapts and stabilizes with agricultural practices. This is in accordance with other studies showing a stable community under long‐term treatments (at least on the DNA level) (de Vries et al , ; Cania et al , ). Moreover, soil organic carbon concentrations peaked at RA6 and decreased at RA12 and RA24 (Pihlap et al , ), likely because organic fertilizers were applied only in the 4th and 7th year of the reclamation process.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the positive effects of RT should be more emphasized in soils with lower clay content, where maintaining high aggregation is more challenging (Cooper et al, 2016). This is in agreement with studies using clayey soils that revealed no differences in aggregate stability when RT and CT were compared (Asgari, 2014;Cania et al, 2019a). However, soil aggregation is a complex process that is driven by both abiotic and biotic factors (Six et al, 2004), and still little is known about how tillage intensity influences soil biota and their capabilities to trigger aggregate formation.…”
Section: Introductionsupporting
confidence: 82%
“…According to Lehmann et al (2017), the bacterial production of adhesive polysaccharides is one of the most crucial biotic mechanisms of soil aggregation. We (Cania et al, 2019a) could show that while the relative abundance of bacteria capable to form EPSs and LPSs was comparable between CT and RT, the community composition of the potential producers of these compounds differed. As the aggregating efficiency of adhesive polysaccharides produced by different taxa varies greatly (Costa et al, 2018), tillage impact on the community composition of EPS and LPS producers could be critical for the stability of agricultural soils.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations